Identifying Bacteria with Public Health Significance from Farmed Nile Tilapia (Oreochromis niloticus), Zambia - Bertha Chitambo; Musso Munyeme; Bernard Hang’ombe (International Journal of Microbiology, 2023)
Zambia has seen rapid development in aquaculture, and in recent years, the industry has experienced disease outbreaks where fish have increasingly become a potential contributor to emerging bacterial zoonotic diseases. The aim of this study was to identify bacterial pathogens with zoonotic potential in apparently healthy fish and water from their habitat. A total of sixty-three fish were sampled, and fifty-nine water samples were collected from the habitats of these fish. Bacteria were cultured from the internal organs of fish and water, and these were identified through standard bacteriological methods comprising morphological characterization, Gram-staining, and a panel of biochemical tests. The following bacterial pathogens with zoonotic potential were identified at a farm prevalence of Aeromonas (13.2%), Bacillus (2.1%), Clostridium (2.1%), Escherichia coli (0.7%), Klebsiella (6.9%), Lactococcus (2.1%), Listeria (0.7%), Staphylococcus (18.1%), and Streptococcus (0.7). Other bacteria with varying significance as fish pathogens identified included Acinetobacter (2.1%), Aequorivita (1.4%), Aerococcus (1.4%), Bordetella (2.1%), Carnobacterium (10.4%), Citrobacter (3.5%), Corynebacterium (1.4%), Dermatophilus (1.4%), Enterococcus (2.1%), Flavobacterium (4.2%), Micrococcus (6.9%), Planococcus (1.4%), Proteus (1.4%), Pseudomonas (6.3%), Rhodococcus (1.4%), Shewanella (1.4%), Streptococcus (0.7%), and Vagococcus (0.7%). The current study provides baseline information for future reference and the implementation of public health guidelines with regard to potential zoonotic diseases in fish.